Riparian Vegetation and Sediment Supply Regulate the Morphodynamic Response of an Experimental Stream to Floods - Lightbody, Anne F.; Kui, Li; Stella, John C.; Skorko, Krysia W.; Bywater-Reyes, Sharon; Wilcox, Andrew C. (Frontiers in Environmental Science, 2019)
Feedbacks between woody plants and fluvial morphodynamics result in co-development of riparian vegetation communities and channel form. To advance mechanistic knowledge regarding these interactions, we measured the response of topography and flow to the presence of riparian tree seedlings with contrasting morphologies in an experimental, field-scale, meandering stream channel with a mobile sand bed. On a convex point bar, we installed seedlings of Tamarix spp. (tamarisk) and Populus fremontii (cottonwood) with intact roots and simulated a bankfull flood, with each of eight runs varying sediment supply, plant density, and plant species. Vegetation reduced turbulence and velocities on the bar relative to bare-bed conditions, inducing sediment deposition when vegetation was present, regardless of vegetation density or species. Sediment supply also played a dominant role, and eliminating sediment supply reduced deposition regardless of the presence of vegetation. Unexpectedly, plant density and species architecture (shrubby tamarisk versus single-stemmed cottonwood) had only a secondary influence on hydraulics and sediment transport. In the absence of plants, mobile bedforms were prominent across the bar, but vegetation of all types decreased the height and lateral extent of bedforms migrating across the bar, suggesting a mechanism by which vegetation modulates feedbacks among sediment transport, topography, and hydraulics. Our measurements and resulting insights bridge the gap between laboratory conditions and real dryland sand-bed rivers and motivate further morphodynamic modeling.